(Co)polymers of oligo(ethylene glycol) methacrylates—temperature‐induced aggregation in aqueous solution. Issue 3 (1st November 2012) - Trzebicka, Barbara; Szweda, Dawid; Rangelov, Stanislav; Kowalczuk, Agnieszka; Mendrek, Barbara; Utrata‐Wesołek, Alicja; Dworak, Andrzej
Abstract The synthesis and aggregation behavior of well‐defined thermosensitive (co)polymers of oligo(ethylene glycol) methacrylates (POEGMA) in aqueous solutions were investigated. The cloud points of the POEGMAs solutions were determined by turbidimetry and dynamic light scattering. For POEGMA (co)polymers the cloud point temperature (TCP) increased linearly with increasing content of more hydrophilic comonomer. The mesoglobules formed by POEGMAs in dilute aqueous solutions above TCP were studied by light scattering. The size of mesoglobules depended on the concentration and the heating procedures. The aggregates became smaller with decreasing initial concentration of polymer and increasing rates of temperature change. By selecting the proper heating and dilution procedures, the influence of the (co)polymer structure on the size of the mesoglobules could be determined. The size of the mesoglobules decreased with the length of the OEG side chains and increased with increasing content of more hydrophilic comonomer. The light scattering parameters of the mesoglobules—A2 values and shape factors <![CDATA[R_gR_h]]> <inline-graphic xlink:href="ark:/27927/pgg1qbqw0nw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />—suggested that the hydrophilic OEG side chains placed at the periphery of the mesoglobules in direct contact with the surrounding water controlled the size of mesoglobules and their stability. Shape factors for all POEGMA mesoglobules indicated that the mesoglobules remained highly hydrated after formation. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013